Pengaruh Kepercayaan dan Kualitas Pelayanan Terhadap Kepuasan Nasabah Cicilan Emas Pada Bank Syariah Indonesia KC Meulaboh Imam Bonjol - Hajar, Siti; Mauliza, Rina (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to use a quantitative approach to the phenomena that occur at BSI KC Meulaboh Imam Bonjol. The data method used in this study is the Accidental Sampling technique with a sample of 86 BSI KC Meulaboh Imam Bonjol customers. The data used are Primary data and Secondary data. The data analysis techniques that will be used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis Test, Hypothesis Testing using SPSS22 Software and Determination Coefficient. The results of this test state that the Influence of Trust and Service Quality Affects Customer Satisfaction of Gold Installments at Bank Syariah Indonesia KC Meulaboh Imam Bonjol.